Biosemiotics comprehension of PrP code and prion disease. (December 2021) - Coca, Juan R.; Eraña, Hasier; Castilla, Joaquín
Abstract: Prions or PrP Sc (prion protein, Scrapie isoform) are proteins with an aberrant three-dimensional conformation that present the ability to alter the three-dimensional structure of natively folded PrP C (prion protein, cellular isoform) inducing its abnormal folding, giving raise to neurological diseases known as Transmissible spongiforms encephalopathies (TSEs) or prion diseases. In this work, through a biosemiotic study, we will analyze the molecular code of meanings that are known in the molecular pathway of PrP C and how it is altered in prion diseases. This biosemiotic code presents a socio-semiotic correlate in organisms that could be unraveled with the ultimate goal of understanding the code of signs that mediates the process. Finally, we will study recent works that indicate possible relationships in the code between prion proteins and other proteins such as the tau protein and alpha-synuclein to evaluate if it is possible that there is a semiotic expansion of the PrP code and prion diseases in the meaning recently expounded by Prusiner, winner of the Nobel Prize for describing these unusual pathological processes.